The Socio, Economic, and Environmental Impacts of Casino Tourism in Goa - Kamat, Kaustubh; Scaglione, Miriam; Kizhakanveatil Bhaskaran Pillai, Subhash; Feng Chen, Ruey (Revista Latino-Americana de Turismologia, 2016)
This study investigates resident perception towards Casino Tourism which may be helpful for the formulation of possible strategic tourism policies. Binary logit model was applied to reveal the heterogeneity of resident’s perception towards casino tourismimpacts. The result of this study reflects the overall opinions of the sample population, and further identifies relatively homogeneous opinion groups. Age, gender, income, education, length of residence was found to have a significant impact on perceptions about casino tourism. Binary logit model and marginal increase function were used to predict increase/decrease in probability to belong to analyzed group by variation in demographic profiles, thus contributing to the debate on casino tourism sustainability.